1994
DOI: 10.1128/jb.176.9.2492-2501.1994
|View full text |Cite
|
Sign up to set email alerts
|

The fas operon of Rhodococcus fascians encodes new genes required for efficient fasciation of host plants

Abstract: Three virulence loci (fas, ftt, and hyp) of Rhodococcus fascians D188 have been identified on a 200-kb conjugative linear plasmid (pFiD188). The fas locus was delimited to a 6.5-kb DNA fragment by insertion mutagenesis, single homologous disruptive recombination, and in trans complementation of different avirulent insertion mutants. The locus is arranged as a large operon containing six open reading frames whose expression is specifically induced during the interaction with host plants. One predicted protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 44 publications
3
65
0
Order By: Relevance
“…In S. griseolus, the structural genes for the ferredoxins of the [3Fe-4S] type are located downstream of their corresponding cytochrome P-450 genes, but there is no evidence for linkage to a ferredoxin reductase gene (55,59). A similar gene organization has been described for the cytochrome P-450 induced in Streptomyces griseus growing in medium with soybean flour (78) and for the fasciation-related cytochrome P-450 with unknown function located on the pFiD188 plasmid of R. fascians (9). The cytochrome P-450 systems induced in R. rhodochrous strains by n-octane (70) or alkoxyphenols and alkoxybenzoates (18,37) and in Rhodococcus chlorophenolicus by pentachlorophenol (80) have not yet been genetically characterized.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In S. griseolus, the structural genes for the ferredoxins of the [3Fe-4S] type are located downstream of their corresponding cytochrome P-450 genes, but there is no evidence for linkage to a ferredoxin reductase gene (55,59). A similar gene organization has been described for the cytochrome P-450 induced in Streptomyces griseus growing in medium with soybean flour (78) and for the fasciation-related cytochrome P-450 with unknown function located on the pFiD188 plasmid of R. fascians (9). The cytochrome P-450 systems induced in R. rhodochrous strains by n-octane (70) or alkoxyphenols and alkoxybenzoates (18,37) and in Rhodococcus chlorophenolicus by pentachlorophenol (80) have not yet been genetically characterized.…”
Section: Discussionmentioning
confidence: 74%
“…A multiple alignment of available sequences for bacterial cytochrome P450s revealed that the Rhodococcus gene represents the first member of a new family, CYP116 (54). The cytochrome P-450 from the fas operon of Rhodococcus fascians, which is required for efficient fasciation of host plants (9), bears little homology with the EPTC-induced cytochrome P-450 from Rhodococcus sp. strain NI86/21.…”
Section: -[Sgnh]-x-[gd]-x-[rhpt]-x-c-[limvfap]-mentioning
confidence: 99%
“…CKs are also produced by a range of various microbial pathogens, including Pseudomonas syringae (Akiyoshi et al, 1987;Morris et al, 1991) and leaf-mining insects (Engelbrecht, 1968), causing the formation of green islands, galls, growth abnormalities, and manipulation of primary carbon metabolism (Balibrea Lara et al, 2004). For several pathogens, it was shown that this CK production is essential for infection (Crespi et al, 1994;Hwang et al, 2010). Based on the induction of sink metabolism by CKs Walters et al, 2008), it has been suggested that the host physiology is altered in response to CKs to allow the pathogen maximum access to nutrients early in (hemi)biotrophic interactions (Walters et al, 2008).…”
mentioning
confidence: 99%
“…The fas locus contains six genes that encode an isopentenyltransferase (IPT) and enzymes involved in the modification of the IPT product. Together they form the machinery for the synthesis of a signal molecule that is essential for symptom development (7,8,48,49). The expression of the fas genes is controlled through a complex network encompassing both transcriptional and translational regulation (50).…”
mentioning
confidence: 99%